PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VA SD NEGERI 75 PEKANBARU - Syakbani, Nispita; Marhadi, Hendri; ', Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT : This research is motivated by the lack of students' mathematics learning outcomes VA State Elementary School 75 of Pekanbaru seen the average value of 68.9 students from 27 students while the minimum completeness criteria established was 74. This research is a classroom action research by applying Problem Based Learning Model. This research aims to improve students' mathematics learning outcomes in class VA State Elementary School 75 of Pekanbaru, the school year 2014/2015. This research was conducted in March-April 2015 the number of students 27 people, 14 boys and 13 girls. This research was conducted by 2 cycles of 6 meetings, consisting of 4 times the presentation of the material and the 2 times daily tests. The instrument used in this study is the teacher and student activity sheets as well as learning about the test results. This research data analysis techniques descriptive analysis techniques. This study presents an increase in the activity of teachers in the first cycle 1 meeting, namely 60% (enough), then increased by 15% at the meeting of 2 to 75% (good). Later in the first meeting of the second cycle increased by 15% to 90% (excellent) and finally in the second cycle 2 meetings increased by 5% to 95% (excellent). Activity of students in the first cycle the first meeting on average 55% (enough), an increase of 15% in the second meeting with the average of 70% (good). Furthermore, the first meeting of the second cycle of activity found students with an average of 85% (excellent) increased 15% in the second meeting with an average of 95% (excellent). Classical learning outcomes before the given action obtained an average grade 68.9 at the end of the first cycle replicates the average value increased to 77.0 an increase of 8.1 (12%) subsequent to the end of the replication cycle II increased to 81,1 an increase of 12.2 (18%). Based on the analysis of these data can be concluded that the adoption of Problem Based Learning Model can improve student learning outcomes math in class VA State Elementary School 75 of Pekanbaru.Keywords: Problem Based Learning Model, Mathematics Learning Outcomes